Formulasi Konsorsium Bakteri Endofit untuk Menekan Infeksi Nematoda Puru Akar Meloidogyne incognita pada Tomat - Ankardiansyah Pandu Pradana; Abdul Munif; Supramana S (Universitas Khairun, 2020)
The root-knot nematodes (Meloidogyne incognita) infection can cause a significant yield loss in tomato plants. One of the environmentally friendly efforts to control this nematode is through the application of endophytic bacteria. The application of endophytic bacteria in the form of a consortium was reported to be more effective than the application using a single isolate. This study aims to test the effectiveness of the endophytic bacteria consortium formula in suppressing M. incognita infection in tomato plants. The research stages were the selection of the consortium of endophytic bacteria as a growth promoter for tomato plants infected with M. incognita. The best performing consortium was formulated using 100 g of grass compost + 100 g vermicompost + 10 ml molasses + 1 g peptone and 50 ml distilled water. The test of bacterial cell viability in the endophytic formula was carried out for 20 weeks. The formula made was tested for its performance as a biocontrol agent against M. incognita in tomato plants. The results showed that three consortia gave the best results as growth promoters of M. incognita infected tomatoes, namely TmtN5, TmtN2, and GsgN2. The three of them survived the formula with log CFU at week 20 of 6.07 (TmtN5), 5.56 (TmtN2), and 6.11 (GsgN2). This formula can suppress the nematode population on tomato plants' roots and suppress the number of root knots in tomato plants. This study provides information that there are three consortia of endophytic bacteria (TmtN5, TmtN2, and GsgN2), which have the potential to become biological control agents for root-purulent nematodes.